1989
DOI: 10.1002/ijc.2910430511
|View full text |Cite
|
Sign up to set email alerts
|

Multiple infections in cases of cervical cancer from a high‐incidence area in tropical Africa

Abstract: The presence of several infections was determined in tissue and serum samples from 34 cases and 23 controls seen in 1984-85 at Mulago Hospital in Kampala, Uganda. When assessing single infections, association with cervical cancer could be shown for 5 agents, namely by Southern blot assay for human papillomavirus types 16 and 18 (HPV), and by serological tests at varying levels of antibody titres, for herpes simplex virus type I and/or 2 (HSV), cytomegalovirus (CMV), Epstein-Barr virus, viral capsid antigen (EB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
2
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(60 citation statements)
references
References 33 publications
(19 reference statements)
3
51
2
3
Order By: Relevance
“…In areas with high-incidence of cervical cancer there seems to be little difference in the prevalence of HPV 16 and HPV 18, whereas in areas with moderately-high incidence, HPV 16 is more common than HPV 18 (27). In the current study we found a higher rate of infection by HPV 18 (30.2%) compared to HPV 16 (27.9%) in the 86 cervical lesions examined.…”
Section: Discussioncontrasting
confidence: 46%
“…In areas with high-incidence of cervical cancer there seems to be little difference in the prevalence of HPV 16 and HPV 18, whereas in areas with moderately-high incidence, HPV 16 is more common than HPV 18 (27). In the current study we found a higher rate of infection by HPV 18 (30.2%) compared to HPV 16 (27.9%) in the 86 cervical lesions examined.…”
Section: Discussioncontrasting
confidence: 46%
“…16,17 Many of the factors that increase both HPV acquisition and promote the oncogenic effect of the virus are also very widespread in Africa. These include: early marriage, polygamous marriages and high parity.…”
Section: Factors Responsible For Cervical Cancer In Africamentioning
confidence: 99%
“…Single women (odds ratio, OR=2.1; 95% confidence interval, CI=1.1-3.9) and illiterate women (OR=1.7; 95% CI=1.1-2.5) showed increased HPV positivity.. High prevalence of HPV in all age groups may be a distinctive feature of populations where HPV transmission continues into middle age and cervical cancer incidence is very high. Many of the factors that increase both HPV acquisition and promote the oncogenic effect of the virus are also very widespread in Africa (Schmauz et al 1989). These include: early marriage, polygamous marriages and high parity.…”
Section: Socio-cultural Factorsmentioning
confidence: 99%